Forty-two-year frequencies of river buffaloes calving in the Terecay ranch, Venezuela - Renny Jesús Becerra; Inés Valentina Reggeti-Gómez; Francisco Miguel Reggeti Gómez; Néstor Simón Montiel-Urdaneta (Revista Científica)
Although buffaloes are polyestrous, they exhibit a distinct seasonal variation in displaying estrus, conception rate, and calving, greatly influenced by physiological, sanitary, nutritional, management, and particularly bioenvironmental factors, such as temperature, humidity, precipitation, evaporation, and daylight duration. Venezuela, a tropical country, is located in the intertropical zone of the northern hemisphere, between the Equator and the Tropic of Cancer, between coordinates 00° 38’ 53” and 12° 11’ 22” LN and 59° 48’ 10” and 73° 25’ 00” LW. The area (Terecay ranch) under study has two well-defined seasons concerning precipitation, with a bimodal behavior, a rainy season (From May to October with an average of 1,441.3 mm/year) and a season with very little or no precipitation (From November to April with an average of 107.4 mm/year). In order to calculate the calving distribution, the records of 13,720 calvings of buffaloes between 1980-2022 corresponding to the Terecay farm located in the Esteros de Camaguan of Guárico State were used. For calculating calving frequency, the PROC FREC procedure of the statistical package SAS version 9.1 was used, and a polynomial regression analysis was performed to evaluate the prediction of future behavior of the calving distribution. The percentage of calving according to the months of the year were: January: 6.96%; February: 4.34%; March: 2.3%; April: 0.95%; May: 0.98%; June: 1.34%; July: 4.39%; August: 11.44%; September: 16.38%; October: 22.32%; November: 15.69% and December 12.91%. The months with the highest average of calving percentages were September (16.38%), October (22.32%), and November (15.69%), and the months with the lowest average percentages were April (0.95%) and May (0.98%). The equation of the polynomial regression analysis was y = -3.0656x4 + 64.363x3 - 360.05x2 + 417.41x + 810.37 with an R² = 0.9571. With this R² value, it can be inferred that the calving behavior will be maintained during these 42 years. Conclusions are that the frequency of calving showed a very marked seasonality between July and January, with 90.09% and 9.91% between February and June. Calving seasonality should be preserved if environmental, nutritional, sanitary, and management conditions are maintained, especially without hormonal interventions.